Noise Amplification in Human Tumor Suppression following Gamma Irradiation - Liu, Bo; Yan, Shiwei; Gao, Xingfa (PloS one, 2011)
The influence of noise on oscillatory motion is a subject of permanent interest, both for fundamental and practical reasons. Cells respond properly to external stimuli by using noisy systems. We have clarified the effect of intrinsic noise on the dynamics in the human cancer cells following gamma irradiation. It is shown that the large amplification and increasing mutual information with delay are due to coherence resonance. Furthermore, frequency domain analysis is used to study the mechanisms.